2016
DOI: 10.2172/1339908
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Model for Volume Fraction of UC, 235U Enrichment, and Effective Density of Final U 10Mo Alloy

Abstract: The purpose of this document is to provide a theoretical framework for (1) estimating uranium carbide (UC) volume fraction in a final alloy of uranium with 10 weight percent molybdenum (U-10Mo) as a function of final alloy carbon concentration, (2) estimating effective 235 U enrichment in the U-10Mo matrix after accounting for loss of 235 U in forming UC and (3) calculating effective density of as-cast U-10Mo alloy with varying enrichment. Therefore, this report will serve as the baseline for quality control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Volume, mass, and density were calculated using Equations 11-13, below: The two densities calculated for Case 1 and Case 2 are 13.44 g/cm 3 and 13.60 g/cm 3 , respectively. The density of 235 UC was estimated to be 13.4394 g/cm 3 in Devaraj et al (2016a), which is consistent with calculations reported here.…”
Section: Ucsupporting
confidence: 91%
See 4 more Smart Citations
“…Volume, mass, and density were calculated using Equations 11-13, below: The two densities calculated for Case 1 and Case 2 are 13.44 g/cm 3 and 13.60 g/cm 3 , respectively. The density of 235 UC was estimated to be 13.4394 g/cm 3 in Devaraj et al (2016a), which is consistent with calculations reported here.…”
Section: Ucsupporting
confidence: 91%
“…UMo matrix density varies with Si concentration from 17.283 to 17.288 g/cm 3 for Case 1, and 17.275to 17.284 g/cm 3 for Case 2. It is noted here that the effective density of the γ-UMo matrix with 19.75 wt% 235 U was previously calculated to be 17.33 g/cm 3 (constant) as is detailed in Devaraj et al (2016a). The UMo matrix density calculated in this report is generally in agreement with that which was previously calculated; however, in this work, we account for variation of the matrix density with 235 U enrichment, which is the reason for the small variation in calculated density values between the 2016 report and this work.…”
Section: Umo Matrixmentioning
confidence: 83%
See 3 more Smart Citations